Rodinný dům - Rycková, Silvie (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Bakalářská práce Rodinný dům je zpracována formou projektové dokumentace obsahující všechny náležitosti dle platných předpisů. Navržený dům se nachází na parcele 121 v obci Dolní Benešov-Zábřeh. Jedná se o novostavbu podsklepeného RD se dvěmi nadzemními podlažími. Dům je pravidelného půdorysu, postaven ze systému PORTHERM a zastřešen sedlovou střechou.

The bachelor project Family house is compiled in a from of project documentation which comprises all the requisites required by current regulations. The designed house is placed on the sites numbered 121 in village Dolní Benešov-Zábřeh. This is a new building with basement with two floors. The house has an regular floor plan, is built from the system POROTHERM and is covered with a gable roof.
Family house
Keywords: Rodinný dům; stavební projekt; technická zpráva; průvodní zpráva; souhrnná technická zpráva; situace; půdorys; řez; pohledy; stropní konstrukce; střecha; betonový základ; železobetonové schodiště; detail.; Family house; construction project; technical report; accompanying report; totality technical report; situation; groud plan; cut; views; overhead construction; roof; concrete foundation; reinforced concrete stairs; detail.